Sleep and dream habits in a sample of French college students who report no sleep disorders. (6th February 2018) - Vallat, Raphael; Eskinazi, Mickael; Nicolas, Alain; Ruby, Perrine
Summary: There is a lack of up‐to‐date data on sleep and dream habits of college students. To fill in this gap, we used an online questionnaire sent to the student mailing lists of two major universities of Lyon (Lyon 1 and Lyon 2) for the recruitment of an functional magnetic resonance imaging study with sleep disorders as exclusion criteria. In the sample (1, 137 French college students, 411 males, mean age = 22.2 ± 2.4 years, body mass index = 22.0 ± 3.2 kg m −2 ), on average, the participants reported spending about 8 hr in bed during weekdays, 9 hr during the weekends, and 90.9% of them reported no difficulty falling asleep. Less than 0.4% of students reported to have sleep‐walking episodes regularly, but nearly 7% reported regular sleep‐talking episodes. The average dream recall frequency was about 3 mornings per week with a dream in mind. Dream recall frequency was positively correlated with the clarity of dream content and the frequency of lucid dreaming, and was negatively correlated with age. Fourteen percent of the students reported frequent lucid dreams, and 6% reported frequent recurrent dreams. We found a gender effect for several sleep and dream parameters, including dream recall frequency and time in bed, both of which were higher in women than in men. We have also observed differences between academic disciplines, namely humanities students (Lyon 2) reported spending more time in bed than sciences students (Lyon 1). These results confirm a gender difference for several sleep and dream parameters, and suggest a link between academic disciplines and sleep duration.